PENGARUH PELATIHAN KERJA, KOMPENSASI DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA PRIME PLAZA HOTEL SANUR DENPASAR - Ni Made Feby Rahayu; I Wayan Widnyana; I Gusti Ngurah Bagus Gunadi (VALUES, 2022)
The current era of globalization and free competition causes many companies to compete to build their employee performance, because employee performance will largely determine the development of the company needed. The low employee performance is one of the factors that can damage the conditions in the company. The factors that can affect employee performance are job training, compensation and organizational culture. The purpose of this study is to determine and analyze the effects of Job Training, Compensation and Organizational Culture on Employee Performance at Prime Plaza Hotel Sanur Denpasar. The sample of this study were 172 employees at Prime Plaza Hotel Sanur Denpasar. Determination of the sample in this study used the Proportional Random Sampling technique by taking proportionally divided samples based on the number of members of each population using Isaac and Michael tables based on an error rate of 5%. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that the job training variables has a positive and significant effect on employee performance. Compensation variables has a positive and significant effect on employee performance. Organizational Culture variables also has a positive and significant effect on employee performance.